Data Protection in a Profiled World
XXIII, 334 p.
Keywords: One of the most challenging issues facing our current information society is the accelerating accumulation of data trails in transactional and communication systems, which may be used not only to profile the behaviour of individuals for commercial, marketing and law enforcement purposes, but also to locate and follow things and actions. Data mining, convergence, interoperability, ever- increasing computer capacities and the extreme miniaturisation of the hardware are all elements which contribute to a major contemporary challenge: the profiled world. This interdisciplinary volume offers twenty contributions that delve deeper into some of the complex but urgent questions that this profiled world addresses to data protection and privacy. The chapters of this volume were all presented at the second Conference on Privacy and Data Protection (CPDP2009) held in Brussels in January 2009 (www.cpdpconferences.org). The yearly CPDP conferences aim to become Europe’s most important meeting where academics, practitioners, policy-makers and activists come together to exchange ideas and discuss emerging issues in information technology, privacy and data protection and law. This volume reflects the richness of the conference, containing chapters by leading lawyers, policymakers, computer, technology assessment and social scientists. The chapters cover generic themes such as the evolution of a new generation of data protection laws and the constitutionalisation of data protection and more specific issues like security breaches, unsolicited adjustments, social networks, surveillance and electronic voting. This book not only offers a very close and timely look on the state of data protection and privacy in our profiled world, but it also explores and invents ways to make sure this world remains a world we want to live in.